Shallot virus X: a hardly known pathogen of the genus Allium - Granda Jaramillo, Roberto (2020)
Crops belonging to the genus Allium, family Amaryllidaceae, are economically important and are widely cultivated around the globe. Some of the most problematic diseases of these crops are caused by members of three virus genera, Potyvirus, Carlavirus and Allexivirus. Shallot virus X (ShVX) is an Allexivirus that was first discovered in Russia in the nineties and it has since been described worldwide. The virus, transmitted mechanically or by the dry bulb mite (Aceria tulipae), affects virtually all members of the genus Allium and it causes yield reductions on these crops. ShVX is a positive-sense single-stranded monopartite RNA virus that contains six open reading frames (ORFs). The virus is mainly detected by RT-PCR but there are other serological and molecular techniques available for diagnosis. There are no methods described for managing crops infected by ShVX in the field, but tissue culture of meristems can render virus-free plants. Research on the ShVX-Allium pathosystem is needed for a comprehensive understanding of the physiological and molecular mechanisms used by the virus to infect its hosts and for developing methods for the effective control of viral infections.